Service Recovery Research: A Review and Future Directions - Sahharwal, Nidhi; Soch, Harmeen Kaur; Kaur, Harsandaldeep (Gyan Management Journal, 2008)
The importance of developing and maintaining relationships with customers is crenerally accepted in marketing terature. Long-term relations with the customers are related to increased sales and profitability of urns. Service failures however, ave the tendency to destroy customer loyalty and thus lead the customers to switch to other service providers. Service recovery is one of the alternatives available with he firm to win back the lost customers and to restore customer satisfaction. Companies that build their reputation in the eyes of their customers by solving their complaints are more likely to develop customer loyalty. The concept of service recovery is becoming increasingly used in management of complaint behavior and companies are making huge investments as a mean of cultivating customer loyalty.